Light‐Coded Digital Crystallinity Patterns Toward Bioinspired 4D Transformation of Shape‐Memory Polymers. (16th March 2020) - Peng, Wenjun; Zhang, Guogao; Liu, Jian; Nie, Shuang; Wu, Yi; Deng, Shihong; Fang, Guangqiang; Zhou, Jian; Song, Jizhou; Qian, Jin; Pan, Pengju; Zhao, Qian; et al.
Abstract: Spatially heterogeneous distribution of active components is key to the diverse shape‐morphing behaviors of biological species and their associated functions. Artificial morphing materials employing similar strategies have widened the design space for advanced functional devices. Typically, the spatial heterogeneity is introduced during the material synthesis/fabrication step and cannot be altered afterward. An approach that allows spatio‐selective programming of crystallinity in a shape‐memory polymer (SMP) by a digital photothermal effect is reported. The light‐patternable crystallinity affects greatly the shape morphing behavior. Consequently, a pre‐stretched 2D film with spatial heterogeneity in crystallinity can morph with time into designable 3D permanent shapes, achieving the 4D transformation. This approach utilizes a reprocessible thermoplastic SMP (polylactide) and the programming relies on a physical phase transformation (crystallization) instead of chemical heterogeneity. This allows repeated erasing and reprogramming using the same material, suggesting a versatile and sustainable means for manufacturing advanced morphing devices. Abstract : Bioinspired 4D transformation is achieved by light‐coding digital crystallinity patterns in a thermoplastic shape memory polymer. The light‐patterned crystallinity introduces spatial heterogeneity that greatly affects the shape morphing behavior, consequently allowing a 2D film to morph with time into a diverse set of designable 3D permanent shapes.